Testing the Psychometric Properties of a Chinese Version of the Level of Expressed Emotion Scale - Wai Tong Chien; Zenobia Chung-Yee Chan; Sally Wai-Chi Chan (The Scientific World Journal)
This study tested the psychometric properties of a Chinese version of the level of expressed emotion scale in Hong Kong Chinese patients with severe mental illness and their family caregivers. First, the semantic equivalence with the original English version and test-retest reliability at 2-week interval of the Chinese version was examined. After that, the reproducibility, construct validity, and internal consistency of the Chinese version were tested. The Chinese version indicated good semantic equivalence with the English version (kappa values = 0.76–0.95 and ICC = 0.81–0.92), test-retest reliability (r = 0.89–0.95, P<0.01), and internal consistency (Cronbach’s α = 0.86–0.92). Among 262 patients with severe mental illness and their caregivers, the 50-item Chinese version had substantial loadings on one of the four factors identified (intrusiveness/hostility, attitude towards patient, tolerance, and emotional involvement), accounting for 71.8% of the total variance of expressed emotion. In confirmatory factor analysis, the identified four-factor model showed the best fit based on all fit indices (χ2/df = 1.93, P=0.75; AGFI = 0.96; TLI = 1.02; RMSEA = 0.031; WRMR = 0.78) to the collected data. The four-factor Chinese version also indicated a good concurrent validity with significant correlations with family functioning (r = −0.54) and family burden (r = 0.49) and a satisfactory reproducibility over six months (intraclass correlation coefficient of 0.90). The mean scores of the overall and subscale of the Chinese version in patients with unipolar disorder were higher than in other illness groups (schizophrenia, psychotic disorders, and bipolar disorder; P<0.01). The Chinese version demonstrates sound psychometric properties to measure families’ expressed emotion in Chinese patients with severe mental illness, which are found varied across countries.